Perceptual and cardiorespiratory responses to high-intensity interval exercise in adolescents: Does work intensity matter? - Malik, A. A.; Williams, C. A.; Weston, K. L.; Barker, A. R. (Journal of Sports Science & Medicine, 2019)
High-intensity interval exercise (HIIE) may not elicit prominent unpleasant feelings even with elevated perceived exertion and physiological stress in adolescents. However, the influence of different HIIE work intensities on the affective experience and cardiorespiratory responses is unknown. This study examined the acute affective, enjoyment, perceived exertion and cardiorespiratory responses to HIIE with different work intensities in adolescents. Participants (n = 16; 8 boys; age 12.0 ± 0.3 years) performed, on separate days, HIIE conditions consisting of 8 x 1-minute work-intervals at 70%, 85%, or 100% peak power separated by 75 seconds recovery at 20 W. Affect, enjoyment and rating of perceived exertion (RPE) were recorded before, during, and after HIIE. Heart rate (HR) and oxygen uptake were collected during HIIE. Affect declined in all conditions (p < 0.01) but 100%HIIE elicited significantly lower affect than 70%HIIE and 85%HIIE at work-interval 8 (all p < 0.02, ES > 1.74; 70%HIIE = 2.5 ± 0.8; 85%HIIE = 1.1 ± 1.5; 100%HIIE = -1.5 ± 1.4 on feeling scale). Similar enjoyment was evident during and after all conditions (all p > 0.44). RPE was significantly higher during 100%HIIE than 70%HIIE and 85%HIIE across all work-intervals (all p < 0.01, ES > 1.56). The majority of the participants attained =90%HRmax during 85%HIIE (87%) and 100%HIIE (100%), but not during 70%HIIE (6%). Affect responses during HIIE are dependent on the intensity of the work-interval and are not entirely negative (unpleasant feelings). Despite similar enjoyment, positive affect experienced during 70%HIIE and 85%HIIE could serve as a strategy to encourage exercise adoption and adherence in adolescents, but only 85%HIIE elicits sufficient HR stimulus to facilitate potential health benefits.